OrthoJacket: an active FES-hybrid orthosis for the paralysed upper extremity - Schill, Oliver; Wiegand, Roland; Schmitz, Bastian; Matthies, Richard; Eck, Ute; Pylatiuk, Christian; Reischl, Markus; Schulz, Stefan; Rupp, Rüdiger (Biomedical engineering, 2011)
The loss of the grasp function in cervical spinal cord injured (SCI) patients leads to life-long dependency on caregivers and to a tremendous decrease of the quality of life. This article introduces the novel non-invasive modular hybrid neuro-orthosis OrthoJacket for the restoration of the restricted or completely lost hand and arm functions in high tetraplegic SCI individuals. The primary goal of the wearable orthosis is to improve the paralysed upper extremity function and, thus, to enhance a patient's independence in activities of daily living. The system combines the advantage of orthotics in mechanically stabilising joints together with the possibilities of functional electrical stimulation for activation of paralysed muscles. In patients with limited capacity, for force generation, flexible fluidic actuators are used to support the movement. Thus, the system is not only intended for functional restoration but also for training. Several sensor systems together with an intelligent signal processing allow for automatic adaptation to the anatomical and neurological individualities of SCI patients. The integration of novel user interfaces based on residual muscle activities and detection of movement intentions by real-time data mining methods will enable the user to autonomously control the system in a natural and cooperative way.
Gesehen am 10.10.2022